Предмет: Математика,
автор: Шоколаднаяфантазия
Помогите решить уравнение 6,3(х+2,4)-9,1(х+1,4) при х=-1,4 Заранее спасибо)
Ответы
Автор ответа:
0
при х=-1,4:
6,3(х+2,4)-9,1(х+1,4)=6,3(-1,4+2,4)-9,1(-1,4+1,4)=6,3*1-9,1*0=6,3
Ответ. 6,3
Автор ответа:
0
упростим
6,3(х+2,4)-9,1(х+1,4)=6,3х+15,12-9,1х-12,74=-2,8х+2,38
подставим
-2,8*-1,4 +2,38=3,92+2,38=6,3
Похожие вопросы
Предмет: История,
автор: kseniapetrova106
Предмет: География,
автор: heybabeily
Предмет: История,
автор: Elllluyt
Предмет: Химия,
автор: dianchoos
Предмет: Математика,
автор: Alla9